(untitled) (Philological Studies, 2020)
The paper discusses a special type of colloquial constructions – discourse formulae, in two languages, Russian and Slovene. The term discourse formulae is applied to the idiomatic multiword dialogical responses like Slovene Kje pa!, Russian Где там!, or English As if! that have their own illocutionary force which emerges through the diachronic process of pragmaticalization. The comparison of the inventory of discourse formulae in multiple languages, and, in particular, in closely related languages, allows to investigate the existing patterns of this process through finding the common strategies and discovering the differences in the development of the pragmatic meaning of a construction. The paper considers the Russian and Slovene discourse formulae that belong to the pragmatic class of negation and presents case studies that illustrate three different types of correlation of discourse formulae between two languages: namely, the full cognates – the discourse formulae with similar internal structure and usage, the false translation equivalents – the discourse formulae having similar internal structure and different function, and the sources of pragmaticalization that are unique for each language but have the same target meaning. The analysis of the semantic and pragmatic meaning of the discourse formulae in the two languages is based on the technique of Moscow Lexical Typology Group which includes the analysis of parallel corpora and the results of a native speakers survey.